Population History and Pathways of Spread of the Plant Pathogen Phytophthora plurivora - Schoebel, Corine N; Stewart, Jane; Gruenwald, Niklaus J; Rigling, Daniel; Prospero, Simone; Gijzen, Mark (PloS one, 2014)
Human activity has been shown to considerably affect the spread of dangerous pests and pathogens worldwide. Therefore, strict regulations of international trade exist for particularly harmful pathogenic organisms. Phytophthora plurivora, which is not subject to regulations, is a plant pathogen frequently found on a broad range of host species, both in natural and artificial environments. It is supposed to be native to Europe while resident populations are also present in the US. We characterized a hierarchical sample of isolates from Europe and the US and conducted coalescent-, migration, and population genetic analysis of sequence and microsatellite data, to determine the pathways of spread and the demographic history of this pathogen. We found P. plurivora populations to be moderately diverse but not geographically structured. High levels of gene flow were observed within Europe and unidirectional from Europe to the US. Coalescent analyses revealed a signal of a recent expansion of the global P. plurivora population. Our study shows that P. plurivora has most likely been spread around the world by nursery trade of diseased plant material. In particular, P. plurivora was introduced into the US from Europe. International trade has allowed the pathogen to colonize new environments and/or hosts, resulting in population growth.